4 Early identification of high-risk individuals for combination monoclonal antibody therapy is feasible by SARS-CoV-2 anti-spike antibody specific lateral flow assay. Issue 5 (26th September 2022) - Pallett, Scott JC; Rayment, Michael; Randell, Paul; Davies, Gary W; Moore, Luke SP
Abstract : Background: Combination monoclonal antibody therapy has recently been approved for prevention and treatment of severe COVID-19 infection in the UK. Available data suggests benefit is limited to those yet to mount an effective immune response from natural infection or vaccination, but concern exists around ability to make timely assessment of immune status of community-based patients. Methods: Healthcare workers were invited to undergo paired laboratory-based and rapid point-of- care (POC) lateral flow anti-spike antibody testing. Three commercial POC tests were selected to represent currently available testing methods: a split IgM/IgG anti-spike antibody test, an anti-receptor binding domain total antibody test and an anti-spike neutralisation assay. Qualitative POC colourmetric band intensities were independently scored and correlated with quantitative IgG neutralising antibody titres (Abbott Architect SARS-CoV-2 IgG Quant II chemiluminescent microparticle immunoassay [CMIA]). CMIA titres were correlated with the World Health Organisation international reference standard for neutralising antibody. Negative controls were carried out using 2018 pre-pandemic sera and post-pandemic individuals with negative CMIA results (target population). Results: 190 individuals (median 40 years, IQR 29-49; 76.2% female) underwent paired testing, with a further 40 pre-pandemic sera tested. Assays demonstrated high performance characteristics: split IgM/IgG assay sensitivity 96.2% (95%CI 92.4.5–98.5), specificity 100.0% (95%CI 91.8–100.0); anti-receptor binding domain total antibody assay sensitivity 100.0% (95%CI 95.5–100.0), specificity 100.0% (95%CI 69.2–100.0). The neutralising antibody assay had a specificity of 97.0% (95%CI 84.2–99.9%) and strongly correlated with neutralising antibody titre (p<0.001). Probability for matched paired results was significant (McNemar's p<0.001) while band intensity correlated strongly with neutralising titres (p<0.0001). Positive and negative predictive values for total antibody and neutralising assays were both >99%. Conclusions: POC assays were found to be reliable predictors of both antibody status and broadly of neutralising antibody titre. Anti-S POC assays have potential to act as suitable alternatives for rapid identification of community patient immune status at presentation.